A continuous hub location model with service constraints for shipping network design. Issue 4 (3rd July 2016) - Zhao, Y. Z.; Zhou, J. M.; Xing, Q. R.
Abstract: We propose a continuous hub location model with service constraints for followers to address the considered problem, describing a situation in which a leader operates a hub-and-spoke shipping network together with a follower who wants to enter into the same shipping market. Subsequently, an augmented Lagrangian function method based on binary entropy function and aggregate function is proposed for the nonlinear 0-1 programming problem. Finally, the conclusions are reached by numerical experiments that, (1) the follower's profits will be the most significant if there are high scale economies, (2) the follower will obtain certain profits by opening a moderate number of hub ports in the case of the service price being considered by consignors even without economies of scale.